Second-Level Digital Divide: Differences in People's Online Skills - Hargittai, Eszter (First Monday, 2002)
Much of the existing literature on the digital divide - the differences between the "haves" and "have nots" regarding access to the Internet - limits its scope to a binary classification of technology use by only considering whether someone does or does not use the Internet. To remedy this shortcoming, in this paper I look at the differences in people's online skills. In order to measure online ability, I assigned search tasks to a random sample of Internet users from a suburban county in the United States. My findings suggest that people search for content in a myriad of ways and there is considerable difference in whether individuals are able to find various types of content on the Web and a large variance in how long it takes to complete online tasks. Age is negatively associated with one's level of Internet skill, experience with the technology is positively related to online skill, and differences in gender do little to explain the variance in the ability of different people to find content online.